2001
DOI: 10.1023/a:1010220930765
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The interaction of three forms of bovine angiotensin-converting enzyme (ACE) with the competitive peptide inhibitor lisinopril with a fluorescent label was studied using fluorescence polarization. The dissociation constants Kd of the enzyme-inhibitor complexes in 50 mM Hepes-buffer (pH 7.5) containing 150 mM NaCl and 1 microM ZnCl2 at 37 degrees C were (2.3 +/- 0.4).10(-8), (2.1 +/- 0.3).10(-8), and (2.1 +/- 0.2).10(-8) M for two-domain somatic ACE, single-domain testicular ACE, and for the N-domain of the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The existence of a ‘silent’ active site is highly unlikely as bovine ACE is highly homologous to the human enzyme, which has two functional active sites. Moreover, in a previous fluorescence polarization study [34] of different bovine ACE forms we showed the presence of two populations of complexes between somatic enzyme and fluorescent‐labeled lisinopril in conditions of a significant lack of the inhibitor; that was attributed to the formation of complexes of labeled lisinopril with different ACE domains.…”
Section: Discussionmentioning
confidence: 69%
“…The existence of a ‘silent’ active site is highly unlikely as bovine ACE is highly homologous to the human enzyme, which has two functional active sites. Moreover, in a previous fluorescence polarization study [34] of different bovine ACE forms we showed the presence of two populations of complexes between somatic enzyme and fluorescent‐labeled lisinopril in conditions of a significant lack of the inhibitor; that was attributed to the formation of complexes of labeled lisinopril with different ACE domains.…”
Section: Discussionmentioning
confidence: 69%
“…In order to identify the features of the initial stages of the formation of vegetation cover on the dump, experimental sites were formed through different combinations of FSL and PFR: option I -application of FSL with a thickness of 0.5 m; option II -control, material of the dump; option IIIapplication of PFR with a thickness of 1 m; option IV -layer-by-layer application of PFR with a thickness of 0.6 m and FSL with a thickness of 0.4 m. [4]. At each site, a series of geobotanical descriptions were carried out (accounting plots with an area of 100 m2) and, the gathering of aboveground phytomass (mowing) was carried out in three iterations on plots with an area of 1 m 2 [5].…”
Section: Methodsmentioning
confidence: 99%
“…Field work was carried out in August 2020. On each trial plot, geobotanical descriptions were carried out according to the standard technique [ 23 ]: the species composition of plants for the herb-dwarf shrub and the moss-lichen aboveground layers, and the projective cover and the height of the tiers were taken into account. Vascular plant species were assigned to seven functional groups: tall shrubs ( Duschekia fruticosa (Rupr.)…”
Section: Methodsmentioning
confidence: 99%